Changes in crop water consumption in Xinjiang of China from 1989 to 2018: A Logarithmic Mean Divisia Index decomposition analysis - Li, Yinbo; Deng, Mingjiang (Frontiers in Environmental Science, 2022)
Xinjiang, located in northwestern China, is the important production base of various crops with high water consumption. The quantitative contribution of driving factors to crop water consumption has been not investigated in Xinjiang. In this study, the logarithmic mean divisia index method is used to quantitatively analyse the effect of five factors (population, planting structure, agricultural economic, water intensity and industrial structure) to crop water consumption during 1989-2018. The results show that (1) crop water consumption has increased from 10.363 to 37.226 billion m3 with a rate of 0.932 billion m3/a in 1989-2018. Its increased trend can be divided into two stages: a slow increase at a rate of 0.425 million m3/a in 1989-2003 and a quick expansion at a rate of 1.310 million m3/a in 2004-2018. (2) The increases of population and agricultural economic both promote crop water consumption, whereas changes in planting structure and water intensity both inhibit crop water consumption. Their contributions are 0.213, 2.068, -0.007 and -0.134 billion m3, respectively. The increased agricultural economic and the decreased water intensity more significantly changed crop water consumption in 2004-2018 than in 1989-2003. (3) The total effects of five factors on crops varied at each stage. All crops (except wheat) have a promoting effect on an increase in crop water consumption with the largest value in cotton (0.378 million m3) in 1989-2003. The effect of five factors on crops (except soybean and medicago) is positive (1.404 million m3) and the highest value is showed in cotton during 2004-2018. The results illustrate the contribution of five factors of crop water consumption and provide references for local agricultural water saving in Xinjiang.